Amoxicillin, a potential epileptogenic drug. Issue 4 (December 2016) - Raposo, João; Teotónio, Rute; Bento, Conceição; Sales, Francisco
Abstract: Beta‐lactams are known to cause a wide spectrum of neurotoxic manifestations including epileptic seizures. The neurotoxicity of penicillin was first reported in 1945 by Johnson and Walker and is believed to exert an inhibitory effect on gamma‐aminobutyric acid transmission of cortical pyramidal cells, due to its beta‐lactam ring structure. Epileptogenicity is also a feature of the semisynthetic beta‐lactams including aminopenicillins. In this report, we present a patient with a recurrent history of discrete body twitching/jerks of epileptic nature in the context of amoxicillin exposure. The EEG revealed intermittent generalized short bursts of beta‐frequency polyspikes. This electro‐clinical picture was reversed by amoxicillin discontinuation.